Risk of complications during hematopoietic stem cell collection in pediatric sibling donors: a prospective European Group for Blood and Marrow Transplantation Pediatric Diseases Working Party study - Styczyński, Jan; Dreger, Peter (Blood, 2012)
We investigated prospectively factors influencing the safety of hematopoietic stem cell (HSC) collection in 453 pediatric donors. The children in the study donated either BM or peripheral blood stem cells (PBSCs) according to center policy. A large variability in approach to donor issues was observed between the participating centers. Significant differences were observed between BM and PBSC donors regarding pain, blood allotransfusion, duration of hospital stay, and iron supplementation; however, differences between the groups undergoing BM vs PBSC donation preclude direct risk comparisons between the 2 procedures. The most common adverse event was pain, reported mainly by older children after BM harvest, but also observed after central venous catheter (CVC) placement for PBSC collection. With regard to severe adverse events, one patient (0.7%) developed a pneumothorax with hydrothorax after CVC placement for PBSC collection. The risk of allotransfusion after BM harvest was associated with a donor age of < 4 years and a BM harvest volume of > 20 mL/kg. Children < 4 years were at higher risk than older children for allotransfusion after BM harvest and there was a higher risk of complications from CVC placement before apheresis. We conclude that PBSC and BM collection are safe procedures in children.